Portuguese Public Higher Education Institutions Investment in Low Density Regions - Case Study - da Costa Sequeira e Sousa Carvalho, Maria Teresa Couceiro; de Sousa Diniz, Francisco Jose Lopes (Economy of Regions, 2020)
Human capital and knowledge have been recognised as important elements in fostering territorial cohesion and sustainable economic development for a long time. In European Union (EU), this recognition was so significant that the European Social Fund was created in the founding Treaty of Rome in 1957, and this support was reinforced in 1972 with the European Regional Development Fund. For their intrinsic nature and mission, Higher Education Institutions (HEIs) not only play an undisputed role in promoting these factors, but also and simultaneously are recognised by their huge spillover effects on the economy of the geographic spaces in which they are included. Since Portugal has become a UE member, these HEIs have benefited from a significant support to investment. The main purpose of this article is to analyse Higher Education Institutions investment between 2000 and 2018, especially focusing on the status of the University of Trás-os-Montes and Alto Douro, both regarding northern institutions, more recent ones and other located in low-density territories. After difficult data collection and subsequent construction of absolute and relative investment indicators, results show that the institutions located in disadvantaged regions had less access to community funds, which can compromise the process of training human capital and knowledge and therefore, the processes of regional convergence and national territorial cohesion. These values are of vital importance for the discussion of ways to enhance the dynamism of these institutions, namely through positive discrimination in access to community funds and ways of facilitating the necessary institutional counterpart in investment financing.